ENGLISH CAMP ACTIVITIES TO INCREASE COMMUNICATIVE SPEAKING ABILITY TO STUDENTS OF STKIP MUHAMMADIYAH MUARA BUNGO - SARI, ARINI KUMALA (Journal Of Language Education and Development (JLed), 2018)
The purpose of this article is to present the result of a study conducted to describe the effect of English camp activities to increase communicative speaking ability to first grade students of STKIP Muhammadiyah Muara Bungo. This study is an action research study based on Kurt.L model which used planning, acting, observing, and reflecting procedures. It was done into two cycles in each cycles consisted of three meetings. The instruments were questionnaire and test. The findings showed that the mean score’s pretest reached of 60,42 to 69,02 and post test’s score reached up to 78,7. It is important to describe that there is a significant improvement of 13,9% to 41,7% in post test 1 and 83,33% in post test 2. Therefore, the criteria of success had been determined. It is crucial to note that using English camp activities have contributed a positive impact on teaching learning process. Clearly, it gives positive improvement on students’ active participation, confidence and their fluency in speaking skill. In short, it can be described that the strategy creates good, enjoyable circumstances and reduces the boredom and stress of learning process.